Molecular Epidemiological Survey of Cryptosporidium in Ochotona curzoniae and Bos grunniens of Zoige County, Sichuan Province - Tian-Cai Tang; Ri-Hong Jike; Liang-Quan Zhu; Chao-Xi Chen; Li-Li Hao (Animals)
In order to investigate the infection status of Cryptosporidium in O. curzoniae and B. grunniens in Zoige County, Sichuan Province, fecal samples from B. grunniens and gastrointestinal contents from captured O. curzoniae were collected between March and December 2023 from five townships (Dazhasi, Axi, Hongxing, Tangke, and Maixi). Genomic DNA was extracted, and nested PCR targeting the small subunit (SSU) rRNA gene of Cryptosporidium was performed. PCR-positive products were sequenced, trimmed, aligned, and subjected to phylogenetic analysis to determine species and genotypes. A total of 242 samples were obtained, of which 20 were Cryptosporidium SSU rRNA-positive, yielding an overall detection rate of 8.3% (20/242). The detection rates of O. curzoniae and B. grunniens were 7.0% (8/114) and 9.4% (12/128), respectively. Among the five sampling sites, Maixi town exhibited the highest detection rate (32.4%, 11/44), followed by Hongxing town (15.2%, 7/46) and Tangke town (4.6%, 2/44). Phylogenetic analysis detected an unidentified Cryptosporidium sp. in O. curzoniae, while C. bovis (n = 10) and C. ryanae (n = 2) were detected in B. grunniens. These findings demonstrate that Cryptosporidium infections are present in both O. curzoniae and B. grunniens in Zoige County, with notable differences in infection rates and species composition. Continued surveillance of Cryptosporidium in local livestock and wildlife is warranted to provide critical data for regional public health management.